Design Of Turbine L On Basin Cylinder Walls With 5cm And 10cm Turbine Distance Various On The Effect Of Electrical Power In The Gravitation Water Vortex Power Plant (GWVPP) - Muhammad Hasan Basri; Muhammad Syaifuddin Zuhri; Hilman Saraviyan Iskawanto; Bachtera Indarto (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2020)
The current source of energy tthat is mostly done in research on renewable energy is water flow. In daily life - electrical energy is widely used by everyone, both young and old. But over time this power source will be exhausted due to continuous use. That is because most of the existing electricity sources come from non-renewable sources. So it is therefore necessary to feel that renewable sources are being used to generate electricity. So the idea emerged to examine a type of small type power plant that is the Water Vortex Power Plant (GWVPP) Generator. Here a study was carried out on the effect of the distance of the L model turbine on the cylindrical basin. For the effective of power in the L model turbine with a distance of 5 cm to the cylinder basin wall is able to produce the highest effective power of 2.89 Watt at a height of 10 cm, while the highest effective power of the L model turbine with a distance of 10 cm towards the cylinder basin wall is 0.14 Watt at 10 cm height from the outlet water output. For the potential power of L model turbines with a distance of 5 cm can produce the highest potential power at an altitude of 28 cm with a potential power of 4.61 watts. While the potential power of the L model turbine with a distance of 10 cm can produce 4.02 watts with a height of 10 cm towards the outlet of the water outlet.